2015
DOI: 10.1111/imm.12457
|View full text |Cite
|
Sign up to set email alerts
|

Gut immune deficits in LEW.1AR1‐iddm rats partially overcome by feeding a diabetes‐protective diet

Abstract: SummaryThe gut immune system and its modification by diet have been implicated in the pathogenesis of type 1 diabetes (T1D). Therefore, we investigated gut immune status in non-diabetes-prone LEW.1AR1 and diabetes-prone LEW.1AR1-iddm rats and evaluated the effect of a low antigen, hydrolysed casein (HC)-based diet on gut immunity and T1D. Rats were weaned onto a cereal-based or HC-based diet and monitored for T1D. Strain and dietary effects on immune homeostasis were assessed in non-diabetic rats (50-60 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…CRAMP’s essential role in maintaining gut microbiota homeostasis may have contributed to the reduced diabetes incidence ( 175 ). Similar results were obtained in the diabetes-prone LEW.1AR1-iddm rat model when fed either the cereal or HC diet, with the HC diet group exhibiting significantly reduced diabetes and Ifng to Il4 mRNA when compared to the cereal group ( 176 ).…”
Section: Environmental Factors and T Cell Phenotype In T1dsupporting
confidence: 76%
“…CRAMP’s essential role in maintaining gut microbiota homeostasis may have contributed to the reduced diabetes incidence ( 175 ). Similar results were obtained in the diabetes-prone LEW.1AR1-iddm rat model when fed either the cereal or HC diet, with the HC diet group exhibiting significantly reduced diabetes and Ifng to Il4 mRNA when compared to the cereal group ( 176 ).…”
Section: Environmental Factors and T Cell Phenotype In T1dsupporting
confidence: 76%
“…HCD has anti-inflammatory and anti-diabetogenic effects in rodent models of T1D, including the BB rat [ 22 , 41 43 ]. Further, antibiotic treatment also protects lymphopenic BB rats from diabetes progression [ 19 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the last 5 years an increasing number of studies using animal models have shown that the intake of dietary fibers plays an important role in maintaining gut microbiota homeostasis; this leads to a delay in the development of T1D ( Table 5 ). For example, feeding LEW.1AR1-iddm rats with a low antigen, hydrolyzed casein-based diet was shown to correct gut immune cell deficits and increase immunoregulatory capacity leading to protection against T1D ( 150 ). Similarly, feeding NOD mice with wheat flour for 72 days shows the same effect with a decrease in the levels of IFN-γ (a proinflammatory cytokine involved in the autoimmune pathogenesis of T1D) and an increase in the levels of IL-10 (an anti-inflammatory cytokine potentially implicated in hindering T1D development) ( 127 ).…”
Section: Future Of T1d Management By Microbiome Therapymentioning
confidence: 99%